Analisis Yuridis Alih Teknologi Dalam Pengadaan Alutsista Sebagai Upaya Revitalisasi Industri Pertahanan Nasional - Alif Fadillah Oemry (Iuris Studia: Jurnal Kajian Hukum, 2021)
The defense industry is a strategic industry that has links with the interests of national defense and security. Indonesia's defense industry needs to be revitalized to support domestic defense and security interests and boost the country's economy. One of the government's efforts to revitalize the defense industry is the transfer of defense equipment technology through the procurement of defense and security equipment from another country. Technology transfer is needed to accelerate the development process so that it does not require a long time in research and defense technology research in producing innovative defense equipment products. This research uses normative legal research supported by primary data. This research will study and analyze the importance of technology transfer, especially in the form of legal regulations in the process of revitalizing the national defense industry, government efforts related to law in developing the defense industry to realize the independence of defense equipment procurement and to find out and analyze the effectiveness of legislation in Indonesia in supporting industrial revitalization national defense through technology transfer. The results of research showed that the legal regulation of technology transfer is very important to protect the intellectual property rights of the technology owner so that the technology owner allows technology transfer, The government uses the concept of the three pillars of the defense industry players in making efforts to develop the national defense industry and the laws and regulations used in the revitalization effort and the defense industry is effective enough to realize the objectives of the revitalization of the defense industry even though it is still not optimal